The Economic Impact of the 2011 Florida BASS Federation Tournament to Osceola County and the Event’s Economic Value to Participants - Sherry Larkin; Jessica Georges; Alan Hodges; Michael Allen; Dale Jones (EDIS, 2012)
The Florida BASS Federation Nation is a chapter of a national organization whose goal is to stimulate public awareness of bass fishing as a major participant sport. Each the state Championship tournament attracts anglers to a competitive event in which participants seek to catch the largest cumulative weight of bass over two days. This article describes an assessment of the economic impact in Osceola County associated with the State Championship tournament. Findings from this analysis should help planners and other stakeholders of similar tournaments better estimate the economic benefits associated with such community activities. This 9-page fact sheet was written by Sherry Larkin, Jessica Georges, Alan Hodges, Michael Allen, and Dale Jones, and published by the UF Department of Food and Resource Economics, October 2012.